2018
DOI: 10.1155/2018/3673515
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Silo Wall Pressure considering the Intermediate Stress Effect

Abstract: The reasonable determination of wall pressure is critical for the design of silo structures. In this study, the primary objective is to present four novel wall pressure coefficients based on four true triaxial strength criteria in the quasiplane strain state. These four strength criteria are the Drucker-Prager (D-P) criterion, the Matsuoka-Nakai (M-N) criterion, the Lade-Duncan (L-D) criterion, and the unified strength theory (UST), and they all consider the effect of the intermediate stress yet to different e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(27 reference statements)
0
6
0
1
Order By: Relevance
“…The lateral pressure act on wall at different depth was given in fig below: The hermetic shallow bin silo has maximum lateral pressure on the top of bin and it gets reduced when it reaches to the bottom of the bin. (Sun, Zhao et al, 2018) [21,22] , also reported the same that the maximum lateral pressure was on the top of the silo bin.…”
Section: Grain Pressure Calculationmentioning
confidence: 91%
See 1 more Smart Citation
“…The lateral pressure act on wall at different depth was given in fig below: The hermetic shallow bin silo has maximum lateral pressure on the top of bin and it gets reduced when it reaches to the bottom of the bin. (Sun, Zhao et al, 2018) [21,22] , also reported the same that the maximum lateral pressure was on the top of the silo bin.…”
Section: Grain Pressure Calculationmentioning
confidence: 91%
“…The lateral pressure for shallow bin silo can be determined using Airy equation. The Rankine Constant (k) can be determined by (Sun, Zhao et al, 2018) [21,22] , and the constant depends on the angle of internal friction (φ) and the angle of internal friction can be taken as natural angle of repose (Sahay and Singh 1996) [22] . He defined k as (1 − sinφ)(1 + sinφ) −1 .…”
Section: Grain Pressure Calculationmentioning
confidence: 99%
“…Apesar da predição das pressões estáticas e dinâmicas constituírem objeto de estudo por vários pesquisadores e muito progresso tenha sido alcançado, ainda não podem ser perfeitamente estimadas (Sun et al, 2018), entretanto, algumas metodologias de cálculos são aceitas por apresentarem boa aproximação, destacando-se as formulações desenvolvidas por Janssen (1985), Reimbert (1943), Jenike e Johanson (1968) e Walker (1966).…”
Section: Pressões Em Silosunclassified
“…Li et al [14] experimentally investigated the stability of the concrete arch under different lateral pressure coefficients. Sun et al [15] derive four wall pressure coefficients in quasiplane strain to consider the intermediate stress effect under four criteria. Tatkoa and Kobielak [16] carry out the laboratory tests in the steel flatbottomed silo model filled with sand.…”
Section: Introductionmentioning
confidence: 99%